The Cipher Code of Simple Sequence Repeats in “Vampire Pathogens” - Zou, Geng (Sci Rep, 2015)
Blood inside mammals is a forbidden area for the majority of prokaryotic microbes; however, red blood cells tropism microbes, like “vampire pathogens” (VP), succeed in matching scarce nutrients and surviving strong immunity reactions. Here, we found VP of Mycoplasma, Rhizobiales, and Rickettsiales showed significantly higher counts of (AG)(n) dimeric simple sequence repeats (Di-SSRs) in the genomes, coding and non-coding regions than non Vampire Pathogens (N_VP). Regression analysis indicated a significant correlation between GC content and the span of (AG)(n)-Di-SSR variation. Gene Ontology (GO) terms with abundance of (AG)(3)-Di-SSRs shared by the VP strains were associated with purine nucleotide metabolism (FDR < 0.01), indicating an adaptation to the limited availability of purine and nucleotide precursors in blood. Di-amino acids coded by (AG)(n)-Di-SSRs included all three six-fold code amino acids (Arg, Leu and Ser) and significantly higher counts of Di-amino acids coded by (AG)(3), (GA)(3), and (TC)(3) in VP than N_VP. Furthermore, significant differences (P < 0.001) on the numbers of triplexes formed from (AG)(n)-Di-SSRs between VP and N_VP in Mycoplasma suggested the potential role of (AG)(n)-Di-SSRs in gene regulation.